Implementation of the School Literacy Movement as a Development of 21st Century Skills: A Case Study of Journalism Extracurricular Activities - Arianto, Anisa Maharani; Mariyadi; Jupitasari, Mellisa; Syahrani, Agus (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
The decline in national literacy and the demands of the 21st century call for innovation in education, particularly in developing critical thinking, communication, collaboration, and creativity. This study aims to analyse the implementation of the School Literacy Movement (GLS) within the Jurnalis SASTRA extracurricular program at SMA Negeri 4 Pontianak as a strategy for fostering 21st-century skills. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving students, a supervising teacher, and the school principal. The findings reveal that integrating GLS into journalistic activities enhances basic literacy (Reading and writing), digital literacy, and cultural literacy. Activities such as news and opinion writing, short film production, poetry, and digital broadcasting develop students’ critical thinking, creativity, and effective communication. Furthermore, teamwork in journalistic production cultivates responsibility, discipline, solidarity, and adaptive collaboration skills. The study also demonstrates that journalistic practice serves as a platform for character education, instilling journalistic ethics and social empathy. Thus, Jurnalis SASTRA is not only a medium for developing 21st-century competencies but also a character education laboratory grounded in literacy. This study recommends strengthening GLS through journalistic approaches as an innovative and practical learning strategy to support curriculum development that is responsive to digital transformation and global challenges.